206k views
5 votes
the first step in determining the solution to the system of equations, y=-x² - 4x-3 and y= 2x + 5, algebraically isthe two equations equal as -x² - 4x - 3= 2x + 5. What is the next step?et y = 0 in y=-x2 - 4x-3.actor each side of the equation.se substitution to create a one-variable equation.ombine like terms onto one side of the equation.

the first step in determining the solution to the system of equations, y=-x² - 4x-example-1

1 Answer

4 votes

Given -

Equations:

y = -x² - 4x -3 and y = 2x + 5

To Find -

Next step =?

Step-by-Step Explanation -

We know first step:

-x² - 4x - 3= 2x + 5

-x² - 4x - 3 - 2x - 5 = 0

-x² - 6x - 8 = 0

-(x² + 6x + 8) = 0

x² + 6x + 8 = 0

x² + 2x + 4x + 8 = 0

x(x+2) +4(x +2) = 0

(x+4)(x+2) = 0

So,

x = -4 or x = -2

So,

The next step is to combine like terms onto one side of the equation.

Final Answer -

Option (d)

Combine like terms onto one side of the equation

User LLS
by
4.4k points